Mechanistic pathways of change in twice weekly versus once weekly sessions of psychotherapy for depression. (April 2022) - Bruijniks, Sanne J.E.; Meeter, Martijn; Lemmens, Lotte; Peeters, Frenk; Cuijpers, Pim; Renner, Fritz; Huibers, Marcus J.H.
Abstract: Background: Recently, we showed that twice weekly sessions of cognitive-behavioral therapy (CBT) and interpersonal psychotherapy (IPT) for depression lead to better and faster treatment outcomes compared to once weekly sessions (Bruijniks et al., 2020 ). The present study investigated which pathways of change may account for the effects of different session frequencies. Method: The sample consisted of 200 patients who were randomized to CBT weekly, CBT twice weekly, IPT weekly, or IPT twice weekly. Outcome and therapy processes were measured at baseline, two weeks and monthly up to month 6 after the start of treatment. Latent change score models investigated temporal relations between change in therapy processes and change in depression and tested whether change in the therapy processes mediated the effect of session frequency on change in depression. Results: IPT skills mediated the relation between session frequency and change in depression. A decrease in depression was related to subsequent improvement in CBT skills and subsequent decrease in motivation for therapy. Conclusion: The development of IPT skills may explain why a twice weekly higher session frequency is more effective in reducing depression compared to a once-weekly session frequency. Future studies should disentangle the causal effects of therapy process change throughout the course of therapy. Highlights: Pathways of change in different session frequencies of psychotherapy for depression. Latent difference score models were used to investigate temporal relations and mediation. IPT skill change mediated the relation between session frequency and depression change. Depression change related to subsequent change in CBT skills, motivation and alliance. IPT skills may explain why a twice weekly higher session frequency is more effective.